Implicit Selective Attention: The Role of the Mesencephalic-basal Ganglia System - Esposito, Matteo; Palermo, Sara; Nahi, Ylenia C.; Tamietto, Marco; Celeghin, Alessia (Current Neuropharmacology, 2024)
The ability of the brain to recognize and orient attention to relevant stimuli appearing in the visual field is highlighted by a tuning process, which involves modulating the early visual system by both cortical and subcortical brain areas. Selective attention is coordinated not only by the output of stimulus-based saliency maps but is also influenced by top-down cognitive factors, such as internal states, goals, or previous experiences. The basal ganglia system plays a key role in implicitly modulating the underlying mechanisms of selective attention, favouring the formation and maintenance of implicit sensory-motor memories that are capable of automatically modifying the output of priority maps in sensory-motor structures of the midbrain, such as the superior colliculus. The article presents an overview of the recent literature outlining the crucial contribution of several subcortical structures to the processing of different sources of salient stimuli. In detail, we will focus on how the mesencephalic- basal ganglia closed loops contribute to implicitly addressing and modulating selective attention to prioritized stimuli. We conclude by discussing implicit behavioural responses observed in clinical populations in which awareness is compromised at some level. Implicit (emergent) awareness in clinical conditions that can be accompanied by manifest anosognosic symptomatology (i.e., hemiplegia) or involving abnormal conscious processing of visual information (i.e., unilateral spatial neglect and blindsight) represents interesting neurocognitive “test cases” for inferences about mesencephalicbasal ganglia closed-loops involvement in the formation of implicit sensory-motor memories.
Keywords: selective attention